STR profiling in a cohort of Saudi patients with acute leukemia - Husein A. Alhatim, PhD Student; Muhammad NH Abdullah, PhD; Suhaili A. Jamaludin, PhD; Armania B. Nurdin, PhD; Sayed A. Amer, PhD (Journal of Taibah University Medical Sciences)
الملخص: أهداف البحث: هدفت هذه الدراسة إلى تحديد ما إذا كانت التكرارات القصيرة الترادفية الجسدية المستخدمة في التعرف الجنائي تختلف في عينات الدم المصابة بسرطان الدم مقارنة بنظيراتها من عينات اللعاب. طريقة البحث: تم جمع الدم واللعاب من 27 مريضا تم تشخيصهم بسرطان الدم الحاد في مدينة الرياض بالمملكة العربية السعودية. تم استخراج الحمض النووي وتم تضخيم 15 موضعا من التكرارات القصيرة الترادفية الجسدية. النتائج: أظهر حوالي 59.3٪ من مرضى سرطان الدم طفرات في مواضع التكرارات القصيرة الترادفية الجسدية. حدث فقدان التماثل الزيجوتي في 40.7٪ من المرضى في (دي19اس433) و (دي16اس539) و (في دبليو ايه) و (دي13اس317) و (تي اتش 01) و (اف جي ايه) و (دي2اس1338). تم الكشف عن عدم استقرار الميكروساتلايت في 22.2٪ منهم في (تي ببي اوه اكس) و (في دبليو ايه) و (دي19اس433) و (دي16اس539) و (دي18اس51). كان (دي19اس433) و (دي16اس539) أكثر المواقع تأثرا حيث أظهرت تغيرات وراثية بنسبة 18.52٪ تليها (في دبليو ايه) (11.11٪) ، بينما كانت (دي2اس1338) و (تي ببي اوه اكس) و (دي18اس51) أقل المواقع تأثرا حيث أظهرت نسبة طفرة بلغت 3.7٪. وأظهرت (دي13اس317) و (تي اتش 01) و (اف جي ايه) طفرة وراثية معتدلة (7.41٪). لم تظهر (سي اس اف 1 ببي اوه) و (دي21 اس11) و (دي3اس1358) و (دي5اس818) و (دي7اس820) و (دي8اس1179) والأميلوجينين تغيرات وراثية في جميع العينات. كان التباين الوراثي العام بين عينات اللعاب والدم مختلفا بشكل كبير . الاستنتاجات: توضح النتائج التي تم الحصول عليها إمكانية استخدام تكرارات قصيرة مترادفة جسمية تستخدم في الطب الشرعي لتشخيص ومراقبة مرضى اللوكيميا. هناك حاجة إلى دراسة أخرى تطبق تقنية التسلسل الجيني للجيل التالي للتحقق من صحة هذه النتائج واستكشاف التطبيقات السريرية لتكرارات قصيرة مترادفة جسمية تستخدم في الطب الشرعي كأدوات تشخيصية لسرطان الدم. Abstract: Objective: This study was aimed at characterizing whether the autosomal short tandem repeats (STRs) used in forensic identification might differ between leukemic blood samples and saliva samples. Methods: Blood and saliva samples were collected from 27 patients diagnosed with acute leukemia in Riyadh City, KSA. DNA was extracted, and 15 STR loci were amplified. Results: Approximately 59.3% of patients with leukemia exhibited mutations at the STR loci. Loss of heterozygosity (LOH) occurred in 40.7% of the patients at D19S433, D16S539, vWA, D13S317, TH01, FGA, and D2S1338. Microsatellite instability (MSI) was detected in 22.2% of patients at TPOX, vWA, D19S433, D16S539, and D18S51. D19S433 and D16S539 were the most affected loci, exhibiting an alteration percentage of 18.52%, followed by vWA (11.11%); in contrast, D2S1338, D18S51, and TPOX were the least affected loci, showing a mutation percentage of 3.7%. D13S317, TH01, and FGA showed moderate genetic mutation (7.41%). CSF1PO, D21S11, D3S1358, D5S818, D7S820, D8S1179, and amelogenin did not show genetic changes in all samples. The overall genetic variability between saliva and blood samples significantly differed (P < 0.001). Conclusion: Our results demonstrate the potential application of forensically used STR loci in diagnosis and monitoring of patients with leukemia. Further study applying next generation sequencing technology is necessary to validate these findings and explore the clinical applications of forensically used STRs as diagnostic tools for leukemia.